Sheikh Ma'ruf al-Nawdhi al-Barzanji (1166-1254 AH/1752-1838 CE) (may God have mercy on him) A study of his writings and scholarly works - Al-Humaid, L. Dr. Barzan Muwassar Hamed (Sulaimani Journal for Humanities, 2024)
It is well known that if a nation wants to rise up and regain its scientific glory and civilizational standing, it must return to its heritage and to the lives and efforts of its scholars and thinkers who enriched scientific life with their efforts, studies, and writings, which fill the libraries of the world in the East and West. Islamic history has recorded the names of distinguished scholars and virtuous thinkers, and it is rare that any book or reference in Islamic sciences is devoid of mentioning them and praising their status. Among them is the subject of our study, the great scholar and eminent Sheikh Maarouf Al-Nawdahi (may God have mercy on him), one of the scholars of Iraqi Kurdistan in the thirteenth century AH/nineteenth century AD. In these pages, we attempt to shed light on his writings and scientific works, both those that are circulated and those that are lost, which have become a source of knowledge for students of science and pioneers of knowledge, and a continuous charity for his soul until the Day of Resurrection.